Reciprocal duties and rights of owner and usurper after delivering the alternate of usurped property - Ã˜Â¹Ã™Â„Ã›ÂŒÃ˜Â´Ã˜Â§Ã™Â‡Ã›ÂŒ Ã™Â‚Ã™Â„Ã˜Â¹Ã™Â‡ Ã˜Â¬Ã™ÂˆÃ™Â‚Ã›ÂŒ, Ã˜Â§Ã˜Â¨Ã™ÂˆÃ˜Â§Ã™Â„Ã™ÂÃ˜Â¶Ã™Â„; Ã˜ÂÃ™Â…Ã›ÂŒÃ˜Â¯Ã›ÂŒ, Ã™Â…Ã˜Â¹Ã˜ÂµÃ™ÂˆÃ™Â…Ã™Â‡; Ã˜Â¨Ã˜Â®Ã˜ÂªÃ›ÂŒÃ˜Â§Ã˜Â±Ã›ÂŒ, Ã˜Â§Ã˜Â¨Ã™ÂˆÃ˜Â§Ã™Â„Ã˜ÂÃ˜Â³Ã™Â† (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Alternate of the usurped property is a compensation paid to the owner after unavailability of usurped property. The Iranian Civil Code, following the Islamic scholars famous view, has principally accepted the payment of this compensation but is silent as far as duties and rights of owner and usurper are concerned; hence the judges obligation to refer to valid verdicts (fatawa) in this regard. In this article, the authors have attempted to analyze the duties and rights of usurper and owner from the perspective of law and Islamic jurisprudence. A review of the rules on the alternate of usurped property indicates that delivering the said alternate does not extinguish the ownerâs right to demand the usurped property and after the removal of unavailability, he is entitled to demand the usurper to return the usurped property. On the other hand, after receiving the alternate, the owner of usurped property may exploit it in any way and, in return, is may not demand compensation for usurped property benefits. In case the alternate is transferred by owner to a third party, the usurper is, after restituting the usurped property, entitled to receive its just mean or price and in the exchange of the usurped property and its alternate, despite the famous view, the right of lien belongs to the usurper.